Penjadwalan Ulang Proyek Pembangunan Perumahan Unit Nabawi Grand Zam Zam dengan Metode Linear Scheduling Method (LSM) - Musa Ghiffary; Rasio Hepyanto; Yosef Cahyo Setitanto P (Universitas Batanghari Jambi, 2026)
Scheduling is one of the crucial aspects in the execution of construction projects, as it directly affects the project's resource requirements. Therefore, an appropriate method is needed to obtain an effective and efficient schedule. This study conducts a rescheduling using the Linear Scheduling Method (LSM) on the Nabawi Grand Zam Zam Housing Project, aiming to provide an alternative schedule for comparison with the initial schedule prepared by the contractor. The data used in this research includes the initial project schedule in the form of an S-curve, along with other supporting data such as the budget plan and the housing site plan. The final result of the LSM calculation, considering the delays, shows that the 68-unit housing project can be completed within 148 working days. This indicates that the schedule produced using the LSM method is more optimal than the existing project schedule, which requires 156 working days (a difference of 8 days). Therefore, based on the conducted research, scheduling using the Linear Scheduling Method can improve time efficiency in project execution.